Phase Change of Low Grade Iron Ore during Sintering and Reduction with Oil Palm Empty Fruit Bunch - Hadi Purwanto (Advanced Aspects of Engineering Research Vol. 2, 2021)
Iron and steel industry is one of the highest carbon dioxide emissions contributors in global carbon dioxide emissions especially in sintering process. In order to reduce pollutant emissions from iron and steel industry, biomass has been widely proposed as an alternative cleaner and renewable fuel. In the iron sintering, it is desirable to substitute coke with biochar since this process contributes a huge amount of greenhouse gases. In this work, coke was substituted with biochar derived from oil palm empty fruit bunch (EFB) as an alternative fuel in the sintering of iron ore. Biochar was produced from EFB at 450°C at a heating rate of 10°C/min, and held for 30 minutes. Sinter was first, prepared by mixing iron ore, biochar, and limestone with water as the binding agent in a ceramic bowl to produce green sample with various ratio biochar and iron ore with fixed 1% limestone. The sinter was examined in terms of ability to remove the oxygen. Apparently, the highest reducibility for the sinter that contains 5% of biochar content is 77.77%. The phase change suggested that at high temperature (1150°C) the sinter can be reduced to metallic iron. The utilization of biochar from EFB as an energy source for sintering of Malaysian iron ore is feasible to produce metallic iron for iron making process. Thus, when the process is applied industrially, it will reduce CO2 emission in iron steel industry by replacing a part of coke as energy source.